CRISPR/Cas9, the Powerful New Genome-Editing Tool for Putative Therapeutics in Obesity - Franco-Tormo, María José (2019)
The molecular technology known as clustered regularly interspaced palindromic repeats (CRISPR)/CRISPR-associated protein (Cas) is revolutionizing the field of medical research and deepening our understanding of numerous biological processes. The attraction of CRISPR/Cas9 lies in its ability to efficiently edit DNA or modulate gene expression in living eukaryotic cells and organisms, a technology that was once considered either too expensive or scientifically risky. CRISPR/Cas9 has been successfully applied in agriculture to develop the next generation of disease-resistant plants. Now, the capability of gene editing has been translated to the biomedical area, focusing on the future of medicine faced with drug-resistant microbes by selectively targeting genes involved in antibiotic resistance, for example, or finding the ultimate strategy for cancer or HIV. In this regard, it was recently demonstrated that an injection of cancer-fighting CRISPR-modified white blood cells in a patient suffering from metastatic lung cancer could lead to promising results. Researchers and bioethicists are debating questions about the regulation of CRISPR/Cas9 that must be addressed. While legal challenges surround the use of this technique for genetically modifying cell lines in humans, we review the basic understanding of CRISPR/Cas9 and discuss how this technology could represent a candidate for treatment of non-communicable diseases in nutrition, such as obesity.